A charge transfer state induced by strong exciton coupling in a cofacial μ-oxo-bridged porphyrin heterodimer. Issue 2 (24th December 2020) - Zarrabi, Niloofar; Bayard, Brandon J.; Seetharaman, Sairaman; Holzer, Noah; Karr, Paul; Ciuti, Susanna; Barbon, Antonio; Di Valentin, Marilena; van der Est, Art; D'Souza, Francis; Poddutoori, Prashanth K.
Abstract : Photodynamics of an aluminum(iii ) porphyrin-phosphorous(v ) porphyrin heterodimer reveals initial formation of a singlet CT state which relaxes to a high-energy triplet CT state lasting for about 105 μs. Abstract : Photosensitizers with high energy, long lasting charge-transfer states are important components in systems designed for solar energy conversion by multistep electron transfer. Here, we show that in a push–pull type, μ-oxo-bridged porphyrin heterodimer composed of octaethylporphyrinatoaluminum(iii ) and octaethylporphyrinatophosphorus(v ), the strong excitonic coupling between the porphyrins and the different electron withdrawing abilities of Al(iii ) and P(v ) promote the formation of a high energy CT state. Using, an array of optical and magnetic resonance spectroscopic methods along with theoretical calculations, we demonstrate photodynamics of the heterodimer that involves the initial formation of a singlet CT which relaxes to a triplet CT state with a lifetime of ∼130 ps. The high-energy triplet CT state ( 3 CT = 1.68 eV) lasts for nearly 105 μs prior to relaxing to the ground state.